(untitled) (Bioresearch Communications, 2021)
Chronic Suppurative Otitis Media (CSOM) is characterized by persistent otorrhoea from the middle ear through a perforated tympanic membrane. It is regarded as one of the most important causes of hearing impairment in developing countries. In many cases, treating CSOM with antibiotics generates fears of resistance. Unlike conventional antibiotics, homeopathic remedies are mostly free from side effects. Therefore, this study was performed to evaluate the effects of homeopathic medicines to treat CSOM patients. A total of 90 subjects were included in this study; among them, 60 were suffering from CSOM, and 30 were healthy controls. The CSOM patients were randomly assigned for the daily administration of homeopathic medicines such as tellurium metallicum in 6C potency (n=17), mercurius solubilis in 200C potency (n=13), and calcarea sulphurica in 30C potency (n=10) for 8 weeks. Ear suppuration was prevented in all of the patients treated with the medicines. More than 50% of the patients’ tympanic membrane perforation were healed by tellurium metallicum and calcarea sulphurica, however, no membrane healing was observed by mercuris solubilis. It was next examined whether the patients underwent hearing impairment compared to healthy control subjects. The average hearing thresholds of the control subjects (n=30) at 1, 4, 8, and 12 kHz frequencies were 13.55 ± 1.57, 15.58 ± 1.12, 27.58 ± 2.00, and 32.57 ± 2.45 dB SPL, respectively. When the average hearing thresholds of the CSOM patients (n=40) were measured at all of the above frequencies, the values became 30.25 ± 1.75, 36.80 ± 3.25, 50.75 ± 2.35, and 59.50 ± 2.96 dB SPL, respectively. This result indicated the loss of hearing in CSOM patients as the average hearing thresholds of the patients were significantly higher (p<0.05) than that of the control subjects. Treatment for 8 weeks with all three homeopathic medicines significantly reduced (p<0.05) hearing thresholds of the patients at all the frequencies. This result demonstrated dramatic improvement in patients’ hearing by the homeopathic medicines. This study, therefore, provides conclusive evidence that homeopathic medicines prevent ear suppuration in CSOM patients as well as heal perforated membrane, and improve hearing. Bioresearch Commu. 7(2): 982-989, 2021 (June)